(untitled) (IITM Journal of Business Studies, 2024)
The COVID-19 pandemic has precipitated unprecedented changes across various sectors, with education being one of the most significantly impacted. As higher education institutions swiftly transitioned from traditional in-person teaching methods to online platforms, the need to assess and understand this digital transformation has become critical. This research paper explores the adoption of online learning tools by higher education institutions in Haryana during the pandemic, employing a qualitative research methodology to gain deeper insights into the experiences, challenges, and outcomes associated with this shift. Utilizing a self-administered questionnaire, the study captures the perspectives of 200 teachers from higher education institutions across Haryana. The questionnaire is designed to probe various facets of the digital transition, including the selection of tools, the effectiveness of online teaching methodologies, the challenges faced by educators in engaging students, and the overall impact on the educational process. Responses will be analyzed to identify patterns and themes that shed light on the effectiveness of the digital tools and strategies implemented during the pandemic.